1990
DOI: 10.1067/mva.1990.16697
|View full text |Cite
|
Sign up to set email alerts
|

Variables that affect the expansion rate and outcome of small abdominal aortic aneurysms

Abstract: Seventy-three patients with small (less than 6 cm in diameter) abdominal aortic aneurysms (AAAs) were selected for nonoperative management and followed up with sequential ultrasound size measurements. Fifty-four men and 19 women, 51 to 89 years of age (mean 70 years), had an initial mean AAA size of 4.1 cm (anteroposterior) x 4.3 cm (lateral) diameter, with a calculated elliptic cross-sectional area of 14.3 cm2. After a mean of 37 months of follow-up, AAA area increased at a mean rate of 20% per year (3 cm2 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 0 publications
4
74
0
8
Order By: Relevance
“…In a similar study of 101 patients with aneurysms measuring less than 5.0 cm in diameter, Valentine et al encountered no ruptures among patients who complied with their follow-up program compared with a 10% rupture rate among those who did not (1217). If continued surveillance is recommended, measures should be taken to control hypertension and to discourage smoking, because these risk factors are associated with accelerated rates of aneurysm growth (936,961). Ultimately, once an infrarenal aortic aneurysm reaches an appropriate size for graft replacement, a choice must be made between a traditional open operation or endovascular repair.…”
Section: Prevention Of Aortic Aneurysm Rupturementioning
confidence: 91%
“…In a similar study of 101 patients with aneurysms measuring less than 5.0 cm in diameter, Valentine et al encountered no ruptures among patients who complied with their follow-up program compared with a 10% rupture rate among those who did not (1217). If continued surveillance is recommended, measures should be taken to control hypertension and to discourage smoking, because these risk factors are associated with accelerated rates of aneurysm growth (936,961). Ultimately, once an infrarenal aortic aneurysm reaches an appropriate size for graft replacement, a choice must be made between a traditional open operation or endovascular repair.…”
Section: Prevention Of Aortic Aneurysm Rupturementioning
confidence: 91%
“…Rupture of aneurysms less than 4 cm in diameter is a rare occurrence, but the expansion rate and the risk of rupture increase exponentially over time once the diameter of the AAA exceeds that measurement (7,8). Importantly, as many as two-thirds of AAAs go unrecognized before rupture, with overall mortality rates approaching 90% once this disaster has occurred (3,9 -12).…”
Section: Introductionmentioning
confidence: 97%
“…16 Cronenwett et al also reported an approximate 10% increase per year. 17 According to our QOL evaluation by the SF-36, of the physical components evaluated, bodily pain worsened postoperatively but recovered within 12 months. Among the mental components, mental health alone improved postoperatively whereas the other three factors did not.…”
Section: Discussionmentioning
confidence: 99%